Kinetics and Mechanism of Oxidation of Amino Acids by Aqueous Bromine - Nalwaya, Nirnajan; Chaturvedi, Gopal; Dashora, Yashwant; Hiran, B.L. (Asian Journal of Chemistry, 2010)
Kinetics of the oxidation of amino acids by bromine solution have been investigated. The reaction has a first order dependence on bromine and amino acids concentrations. The rate of reaction decreases with increase in the concentration of hydrogen ions; order with respect to hydrogen is two. Further, it was observed that first order rate constant decreases with increase in the concentration of bromide ion. This suggests that molecular bromine is not active species in this oxidation; it is probably HOBr. Thermodynamic parameters have been evaluated for each amino acid. A tentative mechanism involving C-C bond fission based on experimental observations has been proposed.